GERAKAN ISLAM POLITIK FUNDAMENTALIS: KASUS HIZBUT TAHRIR INDONESIA DI SURABAYA - Hakim, Rakhmat Nur (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This study aims to qualitatively describe the political conditions that underlie the development of the movement of HizbutTahrir Indonesia (HTI) in Surabaya, ranging from mobilization to the framing which is done to maintain the continuity of the movement. Hizbut Tahrir is one of the movements of Islamic fundamentalism which exists and shows its rapid development in Indonesia. The organization is growing in several main cities, like Surabaya,where a number of universities with excellent quality are located. This article also explains the emergence and development of this movement using social movements theory. The analyis shows that; first,the emergence and establishment of Hizbut Tahrir are influenced by political structures;second,there is a such mobilization and awareness for the framing process, namely a social attribute and awareness of its members in a number of their collective actions.